Coexistence of Light Chain and Transthyretin Cardiac Amyloidosis - Abhishek Gami, MD; John Woller, MD; Paul Scheel, MD; Syed Abbas Ali, MBBS; Carol Ann Huff, MD; Charles Steenbergen, Jr., MD, PhD; Marc Halushka, MD, PhD; Kavita Sharma, MD; Michael Polydefkis, MD; Joban Vaishnav, MD (JACC: Case Reports, 2024)
Although most patients with cardiac amyloidosis are diagnosed with either light chain (AL) or transthyretin (ATTR) disease, coexisting amyloid subtypes can occur. We present three cases of coexisting AL and ATTR cardiac amyloidosis and demonstrate the importance of clinical history and endomyocardial biopsy in diagnosis of this rare entity.